Role of a self-report measure in athlete preparation - Saw, A. E.; Main, L. C.; Gastin, P. B. (The Journal of Strength and Conditioning Research, 2015)
Athlete self-report measures (ASRM) are a common and cost-effective method of athlete monitoring. It is purported that ASRM be used to detect athletes at risk of overtraining, injury, or illness, allowing intervention through training modification. However, it is not known whether ASRM are actually being used for or are achieving these objectives in the applied sport setting. Therefore, the aim of this study was to better understand how ASRM are being used in elite sports and their role in athletic preparation. Semistructured interviews were conducted one-on-one with athletes, coaches, and sports science and medicine staff (n = 30) at a national sporting institute. Interview recordings were transcribed and analyzed for emergent themes. Twelve day-to-day and 7 longer-term practices were identified which contributed to a 4-step process of ASRM use (record data, review data, contextualize, and act). In addition to the purported uses, ASRM facilitated information disclosure and communication among athletes and staff and between staff, and improved the understanding and management of athlete preparation. These roles of ASRM are best achieved through engagement of athletes, coaches, and support staff in the systematic cyclic process.